REVISION AND RE-DOCUMENTATION OF M. AIROLDI'S SPECIES OF LITHOTHAMNION FROM THE TERTIARY PIEDMONT BASIN (NW ITALY) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2010)
The species originally attributed by Airoldi (1932) to the genus Lithothamnion (L. roveretoi, L. obstrusum, L. stefaninii) are here re-examined upon the original material, descriptions and illustrations. L. roveretoi and L. obstrusum are confirmed to belong to the genus Lithothamnion, on the basis of their epithallial and sub-epithallial morphology. L. stefaninii was moved by Fravega (1984) to the genus Archaeolithothamnium, under the nomen novum A. airoldii. In agreement with Fravega, we propose for L. stefaninii Airoldi the new combination Sporolithon airoldii (Fravega). According to ICBN, we select the epitype of Sporolithon airoldii (Fravega) comb. nov. containing both the gametangial and sporangial plants, since the holotype and isotype are ambiguous.
Keywords: Corallinales; Sporolithales; Airoldi type collection; Taxonomy; Stratigraphy